Improved Speaking Skills through The Use of Models of Example Non Example in Students of Grade III Students Elementary School - Nurwaeni, Wiwin; Cahyani, Isah; Rahman, Rahman (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
Speaking skills is a skill that students must master in the 21st century today. This class action study was conducted for 2 cycles with the aim to improve the speech skills of grade III students in elementary school. The subject in this study was a grade III student at SDN 4 Sirnajaya district of Tarogong Kaler Garut Regency, amounting to 19 students consisting of 10 men and 9 women. Data collection methods are conducted by means of tests, interviews, and observations. Listen to data analysis using qualitative and quantitative data analysis techniques. The results showed that there was an increase in the speaking skills of the initial condition or pre-cycle, cycle I through cycle II. At the initial condition or pre-cycle the average value of the students ' speaking ability of 59.21 with a new tunity reaches 22.82%. On the I cycle with the use of model example non example averaging the average speaking ability of students rose to 75.39 with new tunity reaching 47.37%, while on the cycle II the average value of the students ' speaking ability to be 79.51 with a complete determination of 84.22%. Based on the results then the problem formulation in this research can be answered that the use of model example non example can improve the skill of speaking grade III students Elementary School